A Nonsense Consonant-Vowel-Consonant Word Test to Assess Auditory Processing - Cheyney, Mariah Nicole; Moncrieff, Deborah W. (Journal of the American Academy of Audiology, 2018)
Dichotic listening (DL), or how the two ears work together as a team, is often used in the assessment of auditory processing disorders in both children and adults. Currently, the battery of dichotic tests includes stimuli containing words, digits, and nonsense consonant–vowel syllables. Single-syllable nonsense words are of particular use in assessing processing abilities because they can evaluate auditory processing without a listener’s dependence on linguistic knowledge. Therefore, nonsense words may assess auditory processes independently of previous vocabulary knowledge.This study is designed to assess the clinical applicability and face validity of a nonsense word DL test in a young adult population.This study included an experimental design to investigate the performance of young adult listeners on a Dichotic Nonsense Word (DNW) test spoken by a male and female speaker. The results were compared with one study that investigated young adult listener’s performance on dichotic tests of English words.A total of 100 young adult participants were recruited from the School of Health and Rehabilitation Sciences at the University of Pittsburgh to participate in the study. The participants ranged in age from 20 to 30, with an average age of 23, and all participants had normal hearing.DL performance was measured in all participants using the Dichotic Words Test (DWT) and the newly developed DNW test. Kolmogorov–Smirnoff tests of normality were used to assess distribution of right- and left-ear scores. Criterion cutoff scores were determined for the percent correct scores in the nondominant ear and dominant ear and for ear advantage.Scores were significantly different between the two tests in the right ear, Z = −8.258, p < 0.001, and in the left ear, Z = −8.471, p < 0.001. Scores within each test were higher for the right ear than for the left ear, and scores for both ears were significantly lower on the DNW test than for the DWT. Ear advantage scores from the DNW test were significantly larger than those obtained from the DWT. The low and high 95% criterion cutoff ranges for the DNW test were considerably wider than the 95% criterion cutoff ranges for the DWT.Results indicate that the new DNW test may be a useful clinical tool within a test battery for evaluating auditory processing skills independent of vocabulary knowledge.
Keywords: adult; auditory perception; diagnosis; dichotic listening tests/methods; dichotic listening tests/utilization; differential; humans; MeSH terms